Artificial intelligence and smart manufacturing: An analysis of strategic and performance narratives - Alexandra Horobet; Cristiana Doina Tudor; Zeno Dinca; Dan Gabriel Dumitrescu; Eduard Alexandru Stoica (Amfiteatru Economic Journal, 2024)
This paper examines how artificial intelligence and smart manufacturing concepts are reflected in the business strategy and performance narratives of major industrial corporations. A qualitative analysis of annual reports from the 20 largest global industrial companies listed on US stock exchanges was conducted using QDA Miner software. The analysis focused on uncovering connections between smart manufacturing, strategy, and performance themes based on code frequencies, co-occurrences, and proximity, being the first study in the literature with this objective. Through this methodical analysis of the association between smart technologies and the strategic elements of companies in the industrial sector, present in the investor interface represented by annual reports, the article contributes to a better understanding of how technological development has shaped this economic sector. Key findings reveal that while smart manufacturing codes were less frequent, robots and automation , cybersecurity , and sensors displayed higher frequencies, reflecting an emphasis on Industry 4.0 integration. Cluster analysis uncovered a prominent linkage between cybersecurity and strategy/performance codes, highlighting its growing influence. Additionally, concepts such as artificial intelligence , cloud and digitalization showed robust connections with strategy/performance code. The analysis emphasises the strategic prioritisation of technological innovation to enhance operations and competitive positioning. Overall, the study s investigation of annual reports underscores technology s profound impact in shaping strategic objectives, performance frameworks, and operational approaches within the manufacturing sector. The observed correlations illuminate the critical interdependencies between smart manufacturing, strategy formulation, and the realisation of operational excellence. This research contributes valuable qualitative insights into the evolving digital landscape of industrial practices.
Keywords: L60; L21; O32; M21; 330; artificial intelligence (AI); business strategy; corporate performance; qualitative analysis; smart manufacturing